Monitoring of erosive processes near the Serenata Waterfall, in Itambé do Mato Dentro/MG, using nuclearing techniques for its stabilization (Research, Society and Development, 2019)
The erosive processes cause the loss of soil, reducing its fertility and silting up water’s courses. In the region of the Serenata Waterfall, in the municipality of Itambé do Mato Dentro/MG, there are several erosive processes that can cause negatively impact in the tourist potential of this waterfall. In this way, this research aimed to monitor the advance of an erosive process by means of experimental plots and application of the nucleating techniques for its stabilization. For that, the research was carried out by means of the qualitative-quantitative approach, of the descriptive type, carrying out activities in the field, having as universe of the research all the erosive processes in a slope in the region of Cachoeira da Serenata, being chosen a ravine as a practical sample, applying the criterion of non-probabilistic sampling for accessibility. Thus, data collection was used for observation and experimental research, and for data treatment, content analysis and descriptive statistics. Thus, through the satellite image analysis of the years 2006 to 2013, we observed the presence of grazing area and erosive processes in the region of Cachoeira da Serenata, in addition to the 115-meter-long increase in one of the analyzed ravines. During the above-mentioned period, the factors determining the formation of erosive processes, the fragile sandy texture of the soil, the topographic differences of the studied slope, rainfall, sparse vegetation that does not protect the whole soil and infiltration, responsible for the erosion process in the region of Serenata Waterfall. In order to monitor the erosion processes, cuttings and erosion pins were used in experimental plots. It was possible to observe that the plots arranged in a vegetated area did not change, whereas the plots of the vegetation had the largest soil transport in the eleven plots. A total of 12mm of transport, emphasizing the importance of the vegetal cover. Soil transport, artificial perches and transposition of branches to control the erosion process were applied as nucleation techniques. It was possible to perceive the germination of plants and reduction of soil transport due to palisades during two months of application of the techniques.